(untitled) (International Journal of Emerging Trends in Science and Technology, 2017)
Is consciousness a discipline of Philosophy/Theology or Science? Since time immemorial, consciousness has baffled us, bewildered us and sometimes even mystified us. The question still remains that can consciousness be really studied as a rigorous scientific discipline? It is indeed true that the study of consciousness has been now open to various scientific disciplines mostly within the last twenty to thirty years. This has been the case because of the rise of disciplines like neurobiology, cognitive science and even evolutionary biology. Rigorous scientific disciplines have now started considering studies relating to consciousness as not only important but rather imperative towards understanding the brain-mind relationship. In this research paper, I have outlined the main scientific theories that, in my view are studying consciousness rigorously. The first broad scientific discipline that studies consciousness is that of cognitive science and within the broad discipline of cognitive science the main theories are namely, Global Workspace Theory by Bernard Baars, Multiple Drafts Model by Daniel Dennett, Intermediate Level Theory by Ray Jackendoff and finally Information Integration Theory by GuilioTononi and Gerald Edelman. The second broad discipline that studies consciousness scientifically is that of Neurobiology and within the discipline of neurobiology, the main theory would that be of finding the neural correlate of consciousness as proposed by Christof Koch and Francis Crick. The third discipline would also include that of evolutionary biology and within that discipline the most recent work is that of Antonio Damasio and more specifically his book titled Self Comes to Mind.